Temporomandibular disorders and bruxism prevalence in a Portuguese sample - Belo, João (2022)
Communication abstract: Proceedings of the 5th International Congress of CiiEM - Reducing inequalities in Health and Society, held at Egas Moniz’ University Campus in Monte de Caparica, Almada, from June 16th to 18th, 2021. This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.